Target Firm Abnormal Returns and Trading Volume Around the Initiation of Change in Control Transactions - Sanders, Ralph W.; Zdanowicz, John S. (Journal of Financial and Quantitative Analysis, 1992)
Ralph W. Sanders, Jr., John S. Zdanowicz, Target Firm Abnormal Returns and Trading Volume Around the Initiation of Change in Control Transactions, The Journal of Financial and Quantitative Analysis, Vol. 27, No. 1 (Mar., 1992), pp. 109-129